Matrix calculus masquerading as a hydrocalyx secondary to obstructive infundibular renal calculus: a case report - A. V. B., Krishnakanth; L. K., Ganesh; Agarwal, Ankit (International Journal of Research in Medical Sciences, 2024)
Matrix renal calculi are rarely encountered in practice and are difficult to detect and diagnose pre-operatively due to the inability to diagnose on computed tomography. We report a case in which a matrix renal calculus mimicked a hydrocalyx seen in patients with obstructive infundibular renal calculus. A 37-year-old man having chronic kidney disease (CKD) presented with right flank pain and, on evaluation, was diagnosed with right renal calculus. Retrograde pyelography revealed a filling defect in the dilated calyx. Percutaneous nephroscopy into the dilated calyx revealed the presence of matrix component instead of a hydrocalyx secondary to infundibular obstruction. The unique presentation in this case report demonstrates the possibility of matrix calculi in CKD patients with caliectasis secondary to infundibular stone. The rare encounter and ambiguous radiological findings in cases of matrix calculi result in difficulty in prompt diagnosis and surgical management.